SWOT ANALYSIS IN DETERMINING MARKETING STRATEGIES IN MICRO, SMALL AND MEDIUM ENTERPRISES (CASE STUDY OF CAFFE LA'BOSQUE IN KOTABUMI) - Anisa Pitri Sahir; Habiburahman (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2024)
This study aims to determine the marketing strategy in the Caffe La'Bosque business through SWOT analysis, the research method carried out is qualitative descriptive. The number of informants in this study was 10, namely caffe owners, employees and visitors. The analysis used in this study was IFAS, EFAS, IE Matrix and SWOT Matrix. The data collection used is in-depth interviews and observations where researchers come directly to the location to conduct research. Based on the results of the discussion, it was concluded that caffe La'Bosque has the advantages of quality raw materials and has a strategic location where caffe La'bosque is located in the middle of the city in Kotabumi and is in the stadium Sukung Kotabumi and adjacent to schools and offices, the biggest weakness in this company is the lack of marketing carried out where the threat of caffe La'Bosque itself is the number of competitors who have the same business and provide good prices. more tilted so that caffe la'bosque must be more aggressive in promoting so as not to be rivaled, A suitable strategy in doing marketing is horizontal integration which means a marketing strategy carried out to increase profits and sales.